2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1616646
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological and Physiological Effects of Light and Colour on Space Users

Abstract: The impact of colour and light conditions on our emotional and physical health and wellbeing is gaining greater importance in our urban societies. While large resources are allocated for well designed buildings with the right choice of colour and lighting conditions, there are little scientific evidence that supports these choices. The aim of this research was to determine the impact of different colours and lighting conditions on people, using non-invasive means. Close correlations between cardiac activity, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…Color also has an influence on human physiology, such as heart rate, blood pressure, body temperature and vision . Abbas, Kumar and Mclahlan have also studied the impact of color and light on physiological states. The results of this study showed significant changes in heart rate after 2‐min exposures to different colored lights with various intensities.…”
Section: Introductionmentioning
confidence: 99%
“…Color also has an influence on human physiology, such as heart rate, blood pressure, body temperature and vision . Abbas, Kumar and Mclahlan have also studied the impact of color and light on physiological states. The results of this study showed significant changes in heart rate after 2‐min exposures to different colored lights with various intensities.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005 Nadeen Abbas [10] reported that light intensity and colour changes our Heart rate and the influence of this stimulus is subject dependent. This research was conducted by exposing subjects to different colours and light conditions during 110 minutes, but only recorded the last 2 minutes.…”
Section: A Light and Soundmentioning
confidence: 99%
“…Colour light: Abbas (2006) presented a summary of human's perceptions of color lights. Below are some examples of these.…”
Section: Environmental Psychologymentioning
confidence: 99%
“…Our conceptual framework is based on the following: perceptible environmental elements in the atmosphere (space, furniture, equipment, lights, and air) in the idea of Zumthor (2006), Pallasmaa (2014), and Mahmoud (2017); the theory of perceived stimuli in the environment of Russell (1980); positive environmental elements by using various colours and shapes reported by Wright (2018) and Wang & Zhang (2016); positive feelings evoked by color lights in a study by Abbas (2006); positive feelings evoked by background music in the atmosphere, an idea of Herrmann (2009); human, physical, and external factors derived from the concept of finding evidence for design programming of Palmer (1981); combining all environmental elements according to functionality and aesthetics expounded by Rengel (2016); and the concepts of the 5 aspects of a place mentioned above set forth by Craik (1971). The design and development of the interior environment of a leisure learning area in the National Gallery of Thailand was done in 2 steps: design and assessment of the design.…”
Section: Conceptual Frameworkmentioning
confidence: 99%